Creative Accounting Leading to Financial Scams-Evidences from India and USA - Khatri, Dhanesh Kumar (JABM, 2015)
Creative accounting is practically using the flexibility provided within the accountingprinciples or accounting standards to manage recognition, measurement and presentation of different accounting ﬁgures to serve the purpose of those who prepare the accounts rather than those who are likely to use the accounts. Application of creative accounting sk_il.ls beyond a certain limit leads to Financial scam.In the recent past just before Satyam scam was unearthed Satyanfs employee rollrevealed that around 50,000 people were employed in Satyam and US GAAP statement of Satyarn as on 31*‘ March, 2008 disclosed a bank deposit of Rs. 3,400 crores. It raises an eyebrow on the role of statutory auditor Price Waterhouse Corporation PVC-’C). What as an auditor they were doing? Why didn’t they verify the balance with the banker? Accounting scandal of Enron was revealed in October 2001 leading tothe bankruptcy of Enron Corporation and dissolution of one of the auditors of Enronnamely Arther Andersen. Story of Enron scam is not only the biggest scam in the corporate. world of USA but also a biggest question mark on the accounting and auditing regulation in the country like America.Despite of the facts that both of these companies were considered to be good atcorporate governance still their owners i.e. promoters/dnectors self-centered greed led to financial scam. This shows that good governance is only an ornament to cover the ugly face of dirty financial statements.",